2014
DOI: 10.1155/2014/641708
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Keratoconus: Where Do We Stand?

Abstract: Keratoconus is a progressive thinning and anterior protrusion of the cornea that results in steepening and distortion of the cornea, altered refractive powers, and reduced vision. Keratoconus has a complex multifactorial etiology, with environmental, behavioral, and multiple genetic components contributing to the disease pathophysiology. Using genome-wide and candidate gene approaches several genomic loci and genes have been identified that highlight the complex molecular etiology of this disease. The review f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 98 publications
(120 reference statements)
0
64
0
18
Order By: Relevance
“…All of these could probably be the result of a complex interaction of both genetic predisposition and environmental triggering factors, such as eye rubbing and contact lenses wear (the 'two-hit hypothesis') in keratoconus. 42,52,100,113,119,120 conditions in the cornea, will contribute to elucidate these questions and ultimately help to unravel the etiological mysteries of keratoconus. The tear film proteome has become and will stay as an area of high interest for the identification of potential targets for early diagnosis and therapy in these patients, due to its non-invasive nature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these could probably be the result of a complex interaction of both genetic predisposition and environmental triggering factors, such as eye rubbing and contact lenses wear (the 'two-hit hypothesis') in keratoconus. 42,52,100,113,119,120 conditions in the cornea, will contribute to elucidate these questions and ultimately help to unravel the etiological mysteries of keratoconus. The tear film proteome has become and will stay as an area of high interest for the identification of potential targets for early diagnosis and therapy in these patients, due to its non-invasive nature.…”
Section: Resultsmentioning
confidence: 99%
“…3 An important number of locations for genes on chromosomes (loci), 17 of them until now, have been related to keratoconus, thus showing genetic heterogeneity rather than a single major gene effect responsible for development and progression of the disease. 51,52 Some of the genes with reported mutations are SOD1 (locus 21q22.11), VSX1 (locus 20p11.2), and DOCK9 (locus 13q32), which regulate the expression of superoxide dismutase (SOD), photoreceptor cells, and G protein, respectively. [53][54][55] Recently, mutations in MIR184 have been identified as an uncommon cause of keratoconus.…”
Section: Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 KTCN development may be related to environmental factors such as constant eye rubbing or contact lens wear, or it may be genetically controlled. 3 Recently, it was suggested that KTCN could be a quasiinflammatory condition. 4 However, the exact causes of this disease are not well characterized, and its complexity and heterogeneity make it difficult to discover the factors that unambiguously trigger the KTCN phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…However, other patterns of inheritance have also been described. 8 Genetic contribution to the pathogenesis of KTCN is supported by studies showing higher concordance of disease in monozygotic than in dizygotic twins. 9 Several loci implicated in a familial form of KTCN have been reported and there is now a growing list of candidate KTCN genes.…”
Section: Introductionmentioning
confidence: 99%